2014
DOI: 10.1080/10502556.2014.950901
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Window: Regulation of Argumentation and Affect in Custody Mediation

Abstract: High-conflict custody mediation requires working with both the emotional and the factual aspects of the conflict, while balancing unequal power relations between parents. Applying conversation analysis methods to a case of "treatment as usual" high-conflict mediation, this study offers an analysis of the process of establishing a balance point-the mediation window-where both emotional and practical concerns can be discussed efficiently. Communication patterns in the selected case are compared to an extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There is much more to be said about mediation strategies. Our research team has addressed questions about the methodology in other articles (Gulbrandsen , ; Kjøs, Tjersland, and Roen ). Here we comment on the mediator's position and the legal and social context for improving work with HC couples.…”
Section: Discussionmentioning
confidence: 99%
“…There is much more to be said about mediation strategies. Our research team has addressed questions about the methodology in other articles (Gulbrandsen , ; Kjøs, Tjersland, and Roen ). Here we comment on the mediator's position and the legal and social context for improving work with HC couples.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, such issues were addressed with both parents present. In one case, the mediator had separate sessions with each parent before continuing mediation (Kjøs, Tjersland, & Roen, 2014).…”
Section: Focus On the Agreement To Be Reached Vs Focus On Emotions mentioning
confidence: 99%
“…In the total group of thirty‐eight high‐conflict cases in the FORM material, the orderliness of turn‐taking varied greatly (Gulbrandsen, ; Kjøs, Tjersland and Roen, ). In the five cases analysed for the present study, however, all parents adhered to the mediator's suggested discussion format, allowing him to allocate speaking time efficiently, and to initiate shifts between long‐term and short‐term goals, and between relational and factual issues.…”
Section: Mediator Interventionsmentioning
confidence: 99%